Penerapan Model Pembelajaran Think Pair Share untuk Meningkatkan Keteramplan Kerjasama dan Hasil Belajar Siswa - Sulardi Sulardi (Journal of Elementary School (JOES), 2020)
This study aims to prove whether the application of the think pair share learning model in social studies learning can improve cooperation skills and student learning outcomes. The research design used was classroom action research with two learning cycles. The research subjects in this study were fourth grade students of SD Negeri 170 Bengkulu Utara which consisted of 34 students. The research was conducted for two months starting from September 2019 to November 2019. The results showed that the application of the think pair share learning model was proven to be able to improve student cooperation skills in learning, where in the initial test the percentage level of student cooperation skills was 41.18%, increasing in the first cycle of 64.71% and an increase in the second cycle of 88.24%. The application of the learning model is also proven to be able to improve student learning outcomes in social studies learning, where in the initial test the classical completeness level was 35.29%, increased in cycle I to 58.82% and in cycle II increased to 82.35%. In conclusion, the application of the think pair share learning model in social studies learning is effective in improving student collaboration skills and improving student learning outcomes. Keywords: Think Pair Share, Learning Outcomes, Cooperation Skills